(untitled) (International Journal of Islamic Business, 2020)
The purpose of this paper is to develop new instrument that measures the Islamic wealth planning concept based on the Islamic literature. The concept was conceptualized and transformed into an instrument based on two methods, namely experts’ validity (using Lawshe’s technique with eight Malaysian certified Islamic financial planners and two representatives from the official Islamic religious departments in Kedah and Perlis states/Malaysia) and focus group session with seven experts in several related areas, i.e. Islamic philosophy, Islamic finance, and Islamic financial planning. This paper used a quantitative approach using questionnaire. The developed instrument was then distributed to 120 respondents to further improve its validity and two analyses were performed: reliability analysis and exploratory factor analysis. The finding of this study is a new validated instrument for the concept of Islamic wealth planning which contains two main sections, i.e. worldly financial planning and hereafter financial planning. The first section consists of income/investment planning, retirement planning, education (for the individual) planning, and Takaful/insurance planning, while the second section consists of education (for his/her family) planning, Faraid planning, Wasiyyah planning, Zakat/taxes planning, Hajj planning, Hibah planning, Waqf planning, and charitable financial planning. This paper contributes to the existing scarce studies in the area of Islamic wealth planning and management. In addition, this study contributes in transforming the Islamic wealth planning concept into a measurable instrument that can be used for several parties such as Islamic financial planners, high net worth individuals (HNWI) as well as middle class individuals, Islamic financial institutions, and researchers.